METHODICAL APPLICABILITY OF WOMEN'S PLAYING ON THE DEF [TAMBOURINE] IN THE MUSIC EDUCATION - Nikšić, Naka (Metodička teorija i praksa, 2025)
Women's playing of the def [tambourine] in the Novi Pazar area is a music form that is almost unknown to the professional public, and therefore it is not included in the current curriculum. In order to improve the teaching of music classes in Serbia and to preserve this element of culture, we started research in which, using the descriptive method and the technique of content analysis, we looked at the structure of the def, the way and forms of music playing and singing in the Novi Pazar region in the context of customs. We also determined its methodological applicability in teaching according to the requirements of the teaching and learning program from the first to the eighth grade of elementary school. The research results show that it is methodically applicable to content in the fourth and fifth grades of elementary school. In this paper, in accordance with the goals of the program, teachers are given guidelines for processing this music content in accordance with modern methodological trends.
Keywords: Def [tambourine]; Playing on the def; Music content; Content integration; Intercultural education